Robust quantification of fish early life CO(2) sensitivities via serial experimentation - Baumann, Hannes (Biol Lett, 2018)
Despite the remarkable expansion of laboratory studies, robust estimates of single species CO(2) sensitivities remain largely elusive. We conducted a meta-analysis of 20 CO(2) exposure experiments conducted over 6 years on offspring of wild Atlantic silversides (Menidia menidia) to robustly constrain CO(2) effects on early life survival and growth. We conclude that early stages of this species are generally tolerant to CO(2) levels of approximately 2000 µatm, likely because they already experience these conditions on diel to seasonal timescales. Still, high CO(2) conditions measurably reduced fitness in this species by significantly decreasing average embryo survival (−9%) and embryo+larval survival (−13%). Survival traits had much larger coefficients of variation (greater than 30%) than larval length or growth (3–11%). CO(2) sensitivities varied seasonally and were highest at the beginning and end of the species' spawning season (April–July), likely due to the combined effects of transgenerational plasticity and maternal provisioning. Our analyses suggest that serial experimentation is a powerful, yet underused tool for robustly estimating small but true CO(2) effects in fish early life stages.